Diseño de un manual de procesos y procedimientos del área contable de la Empresa Pública ESPAM MFL-EP - Basurto Vidal, Yenny Liseth (2018)
The elaboration of the manual processes and procedures for accounting of the EP spam MFL public company carries out in order to capture in a physical document each of the processes that take place within this Department, so that this becomes in the daily job Guide for the performance of the employees and thus contribute to organizational efficiency. The methodology of certain methods and techniques as the deductive and analytic method made possible the determination of the structure of the design and establishment of strategies to be implemented within the manual in order to improve processes in the area accounting, the same that were identified through the interview to the general manager. Tabs of process design, flow diagrams and description of activities to say that each one of the processes are in a way more understandable and decipherable to the executors, it is worth highlighting that the design of the technical specifications they were useful since they were the initial basis of manual enabling the identification of the sequence of activities involved in the process, the objective of the same, inputs, outputs, suppliers, customers among other aspects, is stresses that this manual contains the description and the procedure of the 5 processes within the accounting department which are: collection and billing, tax, financial statements, budget and payments processing.